1990
DOI: 10.1037/0882-7974.5.1.148
|View full text |Cite
|
Sign up to set email alerts
|

Relations between source amnesia and frontal lobe functioning in older adults.

Abstract: A study is reported in which the relations among normal aging, source amnesia, and frontal lobe functioning were explored. Twenty-four older adults (aged 60-84 years) were tested on their ability to remember where they had acquired new factual information; they were also given the Wisconsin Card Sorting Test (WCST), a test of verbal fluency, and other psychometric tests. The degree of source amnesia in this normal sample correlated with age, verbal fluency, and some measures from the WCST. Source amnesia was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
177
4
4

Year Published

1993
1993
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(200 citation statements)
references
References 13 publications
(17 reference statements)
13
177
4
4
Order By: Relevance
“…Our behavioral results indicated that older adults performed significantly worse on context, but not item, retrieval tasks compared with young adults. This result is consistent with prior source/context memory studies of healthy aging (Craik et al, 1990;Glisky et al, 2001;Cabeza et al, 2002;Cansino et al, 2010). In the following sections, we discuss our volumetric find- ings, the association between MFG volume and retrieval activity and memory performance in young adults, and how healthy aging changes in these patterns of association.…”
Section: Discussionsupporting
confidence: 77%
“…Our behavioral results indicated that older adults performed significantly worse on context, but not item, retrieval tasks compared with young adults. This result is consistent with prior source/context memory studies of healthy aging (Craik et al, 1990;Glisky et al, 2001;Cabeza et al, 2002;Cansino et al, 2010). In the following sections, we discuss our volumetric find- ings, the association between MFG volume and retrieval activity and memory performance in young adults, and how healthy aging changes in these patterns of association.…”
Section: Discussionsupporting
confidence: 77%
“…Poorer performance by the elderly group on temporal discrimination was expected given demonstrationsof comparable phenomena in the elderly (e.g., Craik, Morris, Morris, & Loewen, 1990;McIntyre & Craik, 1987;Schacter, Harbluk, & Mclachlan, 1987). An interesting aspect of the data, however, was that impaired temporal discrimination in the elderly subjects was found when their recognition memory was equal to that of the young divided-attention subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Confabulation is observed in patients with Korsakoff syndrome (Dalla Barba, 1993;Moscovitch, 1995), while false recognition has been reported in a patient with right frontal lesion (Schacter, Curran, Galluccio, Milberg, & Bates, 1996) as well as in normal elderly subjects. Source amnesia, the inability to remember contextual information about the circumstances under which a particular fact was acquired, is impaired in dorsolateral prefrontal patients (Shimamura, 1996), elderly subjects (Craik, Morris, Morris, & Loewen, 1990), and young children (O'Neill & Gopnik, 1991).…”
Section: Future Researchmentioning
confidence: 99%